A crosslinked semiconductive shielding material and a method for its preparation
Patent Information
- Application Number
- CN202611374762.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有技术中,交联型半导电屏蔽料多采用硅烷偶联剂对导电炭黑进行表面改性或直接物理共混,炭黑与聚烯烃基体之间仅依靠弱界面作用结合,冷热循环与长期热老化过程中界面易发生脱粘,导电网络结构遭到破坏;基体多采用单峰分布聚烯烃或通用增韧复配体系,炭黑在基体中缺乏选择性分布的相区结构,导电通路构建效率低且分散均匀性不足;交联工艺多采用分步加料实现时间维度的分步交联或单一均匀交联,无法在空间维度上对导电网络所在相区进行定向交联固定,交联分布不均导致导电网络稳定性与材料韧性难以兼顾
1.本发明通过双键封端1-辛烯齐聚物对导电炉法炭黑进行熔融接枝改性,使炭黑表面形成碳-碳共价键结合的齐聚物分子链层,在基体共混与冷却过程中齐聚物分子链与乙烯-1-辛烯共聚物基体形成拓扑缠结并诱导界面结晶层生长,构建物理锚定与化学键合协同作用的一体化导电网络,与现有技术中采用硅烷偶联剂或简单物理混合的炭黑改性方式相比,可以提高炭黑与基体的界面结合强度以及导电网络在冷热循环和热老化条件下的稳定性,因此可以解决现有半导电屏蔽料中炭黑与基体界面结合弱、长期运行过程中电阻率漂移大、炭黑易迁移脱粘的问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a cross-linked semiconductive shielding material and its preparation method. Background Technology
[0002] Cross-linked semiconductive shielding material effectively alleviates electric field concentration and avoids partial discharge by smoothing conductor surface defects and eliminating air gaps between the insulation layer and the conductor interface. At the same time, its stable semiconductive properties and the heat resistance and deformation resistance after cross-linking can adhere tightly to the insulation layer for a long time, uniformly distribute the radial electric field, and prevent the insulation from premature aging or breakdown due to electrical stress, thereby significantly improving the operational reliability and service life of the cable.
[0003] In existing technologies, cross-linked semiconductive shielding materials often employ silane coupling agents to modify the surface of conductive carbon black or directly physical blend it. The carbon black and the polyolefin matrix rely solely on weak interfacial interactions for bonding, making them prone to debonding during thermal cycling and long-term thermal aging, thus damaging the conductive network structure. Furthermore, the matrix often uses unimodal polyolefins or general toughening compound systems, resulting in a lack of selectively distributed phase regions of carbon black within the matrix, leading to low efficiency in conductive pathway construction and insufficient dispersion uniformity. Cross-linking processes typically employ stepwise feeding to achieve stepwise cross-linking over time or single uniform cross-linking, failing to achieve spatially directional cross-linking and fixation of the conductive network's phase regions. Uneven cross-linking distribution makes it difficult to balance conductive network stability and material toughness. These issues collectively affect the balance between conductive stability, interfacial bonding strength, and mechanical properties of semiconductive shielding materials during long-term operation. Therefore, this invention provides a cross-linked semiconductive shielding material and its preparation method. Summary of the Invention
[0004] The purpose of this invention is to provide a cross-linked semi-conductive shielding material and its preparation method. This invention involves melt grafting modification of conductive furnace carbon black using a double-bond-terminated 1-octene oligomer, forming a carbon-carbon covalently bonded oligomer molecular chain layer on the carbon black surface. This layer forms topological entanglement with the ethylene-1-octene copolymer matrix and induces the growth of an interfacial crystalline layer, constructing an integrated conductive network with synergistic physical anchoring and chemical bonding. A bimodal crystallinity distribution matrix is formed by compounding low-crystallinity and high-crystallinity ethylene-1-octene copolymers, allowing the carbon black to spontaneously and selectively distribute in the amorphous phase region to construct an efficient conductive pathway. A single peroxide cross-linking agent utilizes the difference in solubility in the phase region to create a preferential cross-linking distribution in the amorphous phase. The main cross-linking reaction is fully completed during the melt blending stage, and a three-stage programmed temperature-controlled crystallization process completes the growth of the interfacial crystalline layer and the system's final shape, thereby improving the long-term stability of the conductive network, the interfacial bonding strength between the carbon black and the matrix, and the balance between the material's mechanical and conductive properties.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A cross-linked semi-conductive shielding material, by weight, comprises the following components: 80-85 parts of olefin matrix resin, 18-22 parts of oligomer graft-modified conductive carbon black, 1.0-1.5 parts of peroxide cross-linking agent, and 0.5-1.0 parts of processing aid; The olefin-based resin is composed of a bimodal ethylene-1-octene copolymer blend and high-density polyethylene; the bimodal ethylene-1-octene copolymer blend is used in an amount of 72-80 parts, and is composed of a low-crystallinity ethylene-1-octene copolymer and a high-crystallinity ethylene-1-octene copolymer in a mass ratio of 55:45-65:35; the high-density polyethylene is used in an amount of 5-8 parts, and has a density of 0.945-0.955 g / cm³. 3 The melt index measured at 190℃ and 2.16kg load is 5-8g / 10min; the sum of the amounts of the bimodal crystallinity distribution ethylene-1-octene copolymer compound and the high-density polyethylene is 80-85 parts. The oligomer-grafted modified conductive carbon black is obtained by melt grafting of double-bond-terminated 1-octene oligomers onto conductive furnace black as the base material; the number average molecular weight of the double-bond-terminated 1-octene oligomers is 1500-2500, the double bond functionality is 1.8-2.0, and the grafting amount is 2.0%-3.0% of the mass of the conductive furnace black; The peroxide crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide; The processing aid consists of antioxidants and lubricants.
[0006] Preferably, the low-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 24%–28%, a crystallinity of 5%–10%, and a weight-average molecular weight of 200,000–250,000; the high-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 8%–12%, a crystallinity of 45%–55%, and a weight-average molecular weight of 80,000–100,000.
[0007] Preferably, the original particle size of the conductive furnace carbon black is 20-30 nm, the DBP absorbance is 38-42 mL / 100 g, and the specific surface area is 420-480 m². 2 / g; the melt grafting uses dicumyl peroxide as an initiator, and the amount is 0.1% to 0.2% of the mass of the conductive furnace carbon black.
[0008] Preferably, the 1-minute half-life temperature of the 2,5-dimethyl-2,5-di-tert-butylperoxide is 178–182 °C.
[0009] Preferably, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the dosage is 0.3 to 0.6 parts; the lubricant is zinc stearate, and the dosage is 0.2 to 0.4 parts.
[0010] Preferably, the preparation method includes the following steps: Step S1, Preparation of oligomer-grafted modified conductive carbon black: Conductive furnace black, double-bond-terminated 1-octene oligomer, and dicumyl peroxide are premixed and then fed into a twin-screw extruder for melt mechanochemical grafting. After extrusion and granulation, grafted modified carbon black is obtained; the amount of dicumyl peroxide is 0.1% to 0.2% of the mass of the conductive furnace black. Step S2, bimodal matrix premix: Low-crystallinity ethylene-1-octene copolymer, high-crystallinity ethylene-1-octene copolymer, and high-density polyethylene are added to a high-speed mixer in proportion and mixed evenly to obtain a matrix premix. Step S3, Blending Extrusion Crosslinking: The matrix premix, grafted modified conductive carbon black, peroxide crosslinking agent and processing aid are added to a twin-screw extruder, melt-blended and the main crosslinking reaction is completed. The crosslinking distribution tendency of amorphous phase is formed by taking advantage of the solubility difference of peroxide in different microphase regions, and the melt is extruded to obtain the melt. Step S4, temperature-controlled crystallization and shaping: The extruded melt enters a segmented temperature-controlled cooling water tank, where it is melt-blended and subjected to gradient cooling to complete the surface interface crystallization growth and system shaping of carbon black, accompanied by trace amounts of subsequent crosslinking reactions; Step S5 involves traction pelletizing to obtain cylindrical finished pellets with a diameter of 3-4 mm and a length of 3-5 mm.
[0011] Preferably, in step S1, the length-to-diameter ratio of the twin-screw extruder is 40:1, the temperature of each section is 165-180℃, the screw speed is 300-350rpm, and the material residence time is 40-50s.
[0012] Preferably, in step S2, the mixing temperature of the high-speed mixer is 80-90°C, the rotation speed is 1200-1500 rpm, and the mixing time is 5-7 min.
[0013] Preferably, in step S3, the length-to-diameter ratio of the twin-screw extruder is 40:1, the temperature from the feeding section to the melting section is 120-140°C, the temperature from the homogenization section to the die is 165-180°C, the screw speed is 280-320 rpm, and the total residence time of the melt-blended and gradient-cooled material is 50-60 s, ensuring that the peroxide is fully decomposed in the melting section and completes the main cross-linking reaction.
[0014] Preferably, the specific parameters for segmented temperature control in step S4 are as follows: The water temperature in the first cooling section, i.e. the nucleation section, is kept constant at 95–100°C, and the melt residence time is 2–3 minutes. The water temperature in the second cooling section, i.e. the transverse crystal growth section, is linearly reduced to 85-90℃ at a rate of 3℃ / min, and held at a constant temperature for 5-7 minutes. The water temperature in the third cooling section, also known as the shaping section, is 20–25°C.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention modifies conductive furnace carbon black by melt grafting with double-bond-terminated 1-octene oligomers, forming a carbon-carbon covalently bonded oligomer molecular chain layer on the carbon black surface. During matrix blending and cooling, the oligomer molecular chains form topological entanglement with the ethylene-1-octene copolymer matrix and induce the growth of an interfacial crystalline layer, constructing an integrated conductive network with synergistic effects of physical anchoring and chemical bonding. Compared with existing carbon black modification methods using silane coupling agents or simple physical mixing, this invention can improve the interfacial bonding strength between carbon black and the matrix, as well as the stability of the conductive network under thermal cycling and thermal aging conditions. Therefore, it can solve the problems of weak interfacial bonding between carbon black and the matrix, large resistivity drift during long-term operation, and easy migration and debonding of carbon black in existing semiconductive shielding materials.
[0016] 2. This invention utilizes a bimodal crystallinity distribution matrix formed by blending low-crystallinity ethylene-1-octene copolymer and high-crystallinity ethylene-1-octene copolymer in a specific ratio. This allows conductive carbon black to spontaneously and selectively distribute in the low-crystallinity amorphous phase region based on surface energy differences, forming a continuous and efficient conductive pathway. Simultaneously, the high-crystallinity component provides mechanical strength and heat resistance. Compared with existing technologies using unimodal distribution polyolefins or general toughening compound systems, this invention can improve the construction efficiency of the conductive network and the balance between the material's mechanical and conductive properties. Therefore, it can solve the problems of poor carbon black dispersion, low conductive pathway construction efficiency, and difficulty in simultaneously achieving mechanical and conductive properties in existing semiconductive shielding materials.
[0017] 3. This invention uses 2,5-dimethyl-2,5-di-tert-butylperoxide as a single crosslinking agent, utilizing the difference in solubility between the amorphous and crystalline phases to create a preferential crosslinking distribution in the amorphous phase. The main crosslinking reaction is fully completed during the melt blending stage. Combined with a three-stage temperature-controlled crystallization process, the growth of the crystalline layer at the carbon black surface interface and the shaping of the system are completed. Compared with the existing technologies that use stepwise feeding and time-dimensional crosslinking or single uniform crosslinking, this invention can improve the degree of crosslinking fixation in the phase region where the conductive network is located, as well as the overall toughness and processing fluidity of the material. Therefore, it can solve the problems of uneven crosslinking distribution, insufficient fixation of the conductive network, and processing difficulties caused by excessive crosslinking or decreased mechanical properties caused by excessively low crosslinking in existing semiconductive shielding materials. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention have been clearly and completely described. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] This embodiment provides a cross-linked semi-conductive shielding material, which, by weight, comprises the following components: 80-85 parts of olefin matrix resin, 18-22 parts of oligomer graft modified conductive carbon black, 1.0-1.5 parts of peroxide cross-linking agent, and 0.5-1.0 parts of processing aid; The olefin-based resin is composed of a bimodal ethylene-1-octene copolymer blend and high-density polyethylene; the bimodal ethylene-1-octene copolymer blend is used in an amount of 72-80 parts, and is composed of a low-crystallinity ethylene-1-octene copolymer and a high-crystallinity ethylene-1-octene copolymer in a mass ratio of 55:45-65:35; the high-density polyethylene is used in an amount of 5-8 parts, and has a density of 0.945-0.955 g / cm³. 3 The melt index measured at 190℃ and 2.16kg load is 5-8g / 10min; the sum of the amounts of the bimodal crystallinity distribution ethylene-1-octene copolymer compound and the high-density polyethylene is 80-85 parts. The oligomer-grafted modified conductive carbon black is obtained by melt grafting of double-bond-terminated 1-octene oligomers onto conductive furnace black as the base material; the number average molecular weight of the double-bond-terminated 1-octene oligomers is 1500-2500, the double bond functionality is 1.8-2.0, and the grafting amount is 2.0%-3.0% of the mass of the conductive furnace black; The peroxide crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide; The processing aid consists of antioxidants and lubricants. The amount of antioxidant is verified by crosslinking efficiency matching to avoid significant offsetting effects on the main crosslinking reaction.
[0020] In some embodiments, the low-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 24%–28%, a crystallinity of 5%–10%, and a weight-average molecular weight of 200,000–250,000; the high-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 8%–12%, a crystallinity of 45%–55%, and a weight-average molecular weight of 80,000–100,000.
[0021] In some embodiments, the original particle size of the conductive furnace carbon black is 20–30 nm, the DBP absorbance is 38–42 mL / 100 g, and the specific surface area is 420–480 m². 2 / g; The melt grafting uses dicumyl peroxide as an initiator, with a dosage of 0.1% to 0.2% of the mass of carbon black from the conductive furnace method. By controlling the initiator feeding ratio and reaction residence time, the self-polymerization side reaction of the oligomer is suppressed.
[0022] In some embodiments, the 1-minute half-life temperature of the 2,5-dimethyl-2,5-di-tert-butylperoxide is 178–182 °C.
[0023] In some embodiments, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], used in an amount of 0.3 to 0.6 parts; the lubricant is zinc stearate, used in an amount of 0.2 to 0.4 parts.
[0024] In some embodiments, the preparation method includes the following steps: Step S1, Preparation of oligomer-grafted modified conductive carbon black: Conductive furnace black, double-bond-terminated 1-octene oligomer, and dicumyl peroxide are premixed and then fed into a twin-screw extruder for melt mechanochemical grafting. After extrusion and granulation, grafted modified carbon black is obtained; the amount of dicumyl peroxide is 0.1% to 0.2% of the mass of the conductive furnace black. Step S2, bimodal matrix premix: Low-crystallinity ethylene-1-octene copolymer, high-crystallinity ethylene-1-octene copolymer, and high-density polyethylene are added to a high-speed mixer in proportion and mixed evenly to obtain a matrix premix. Step S3, Blending Extrusion Crosslinking: The matrix premix, grafted modified conductive carbon black, peroxide crosslinking agent and processing aid are added to a twin-screw extruder, melt-blended and the main crosslinking reaction is completed. The crosslinking distribution tendency of amorphous phase is formed by taking advantage of the solubility difference of peroxide in different microphase regions, and the melt is extruded to obtain the melt. Step S4, temperature-controlled crystallization and shaping: The extruded melt enters a segmented temperature-controlled cooling water tank, where it is melt-blended and subjected to gradient cooling to complete the surface interface crystallization growth and system shaping of carbon black, accompanied by trace amounts of subsequent crosslinking reactions; Step S5 involves traction pelletizing to obtain cylindrical finished pellets with a diameter of 3-4 mm and a length of 3-5 mm.
[0025] In some embodiments, the length-to-diameter ratio of the twin-screw extruder in step S1 is 40:1, the temperature of each section is 165-180°C, the screw speed is 300-350 rpm, and the material residence time is 40-50 s.
[0026] In some embodiments, the mixing temperature of the high-speed mixer in step S2 is 80-90°C, the rotation speed is 1200-1500 rpm, and the mixing time is 5-7 min.
[0027] In some embodiments, the length-to-diameter ratio of the twin-screw extruder in step S3 is 40:1, the temperature from the feeding section to the melting section is 120-140°C, the temperature from the homogenization section to the die is 165-180°C, the screw speed is 280-320 rpm, and the total residence time of the melt-blended and gradient-cooled material is 50-60 s, ensuring that the peroxide is fully decomposed in the melting section and completes the main crosslinking reaction.
[0028] In some embodiments, the specific parameters for segmented temperature control in step S4 are: The water temperature in the first cooling section, i.e. the nucleation section, is kept constant at 95–100°C, and the melt residence time is 2–3 minutes. The water temperature in the second cooling section, i.e. the transverse crystal growth section, is linearly reduced to 85-90℃ at a rate of 3℃ / min, and held at a constant temperature for 5-7 minutes. The water temperature in the third cooling section, also known as the shaping section, is 20–25°C.
[0029] Based on the foregoing embodiments, the following sets of embodiments were implemented: It should be noted that the raw materials used in the following examples are all commercially available industrial-grade raw materials.
[0030] The raw material properties used in the following examples were all tested using a unified method: crystallinity was tested using differential scanning calorimetry (DSC) and calculated using the standard enthalpy of crystallization of polyethylene (293 J / g); weight-average molecular weight was tested using high-temperature gel permeation chromatography (GPC) with polystyrene as the standard and 1,2,4-trichlorobenzene as the solvent at a test temperature of 150°C; DBP absorbance was tested according to GB / T3780.2-2017; specific surface area was tested according to the CTAB method of GB / T3780.5-2017; double bond functionality was tested using iodometric titration, i.e., the average number of double bonds on each oligomer molecular chain; grafting amount was calculated by thermogravimetric analysis after removing ungrafted oligomers using Soxhlet extraction; and the 1-minute half-life temperature was tested using differential scanning calorimetry (DSC), taking the temperature corresponding to a decomposition half-life of 1 minute.
[0031] Example 1: A cross-linked semiconductive shielding material, comprising the following components by mass: 82 parts olefin matrix resin, 20 parts oligomer grafted modified conductive carbon black, 1.2 parts peroxide cross-linking agent, and 0.7 parts processing aid.
[0032] The olefin-based resin contains 75 parts of a bimodal crystallinity distribution ethylene-1-octene copolymer compound, with a mass ratio of low-crystallinity ethylene-1-octene copolymer to high-crystallinity ethylene-1-octene copolymer of 60:40; and 7 parts of high-density polyethylene.
[0033] The low-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 26%, a crystallinity of 7%, and a weight-average molecular weight of 220,000; the high-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 10%, a crystallinity of 50%, and a weight-average molecular weight of 90,000.
[0034] In the oligomer-grafted modified conductive carbon black, the original particle size of the conductive furnace carbon black is 25 nm, the DBP absorbance is 40 mL / 100 g, and the specific surface area is 450 m². 2 / g; the number average molecular weight of the double-bond-terminated 1-octene oligomer is 2000, the double bond functionality is 1.9, and the grafting amount is 2.5% of the mass of conductive furnace carbon black; the amount of dicumyl peroxide is 0.15% of the mass of conductive furnace carbon black. By controlling the initiator feeding ratio and reaction residence time, the self-polymerization side reaction of the oligomer is suppressed.
[0035] The peroxide crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide.
[0036] The processing aids include 0.4 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.3 parts of zinc stearate. The amount of antioxidant was verified by crosslinking efficiency matching to avoid significant offsetting effects on the main crosslinking reaction.
[0037] The preparation method of the cross-linked semiconductive shielding material includes the following steps: Step S1, Preparation of oligomer grafted modified conductive carbon black: Conductive furnace carbon black, double bond-terminated 1-octene oligomer, and dicumyl peroxide are added to a high-speed mixer and premixed at 80℃ and 1200rpm for 3 minutes. Then, the mixture is added to a twin-screw extruder with an aspect ratio of 40:1. The temperature of each section is set at 170℃, the screw speed is 320rpm, and the material residence time is 45s. The free radicals generated by the thermal decomposition of dicumyl peroxide, combined with the dispersion promoting effect of melt shear, initiate the oligomer molecules to graft onto the defect sites on the carbon black surface, completing the melt mechanochemical grafting reaction. The reaction conditions are controlled to suppress the oligomer self-polymerization side reaction. The grafted modified carbon black is obtained by extrusion granulation.
[0038] Step S2, bimodal matrix premix: Low-crystallinity ethylene-1-octene copolymer, high-crystallinity ethylene-1-octene copolymer, and high-density polyethylene are added to a high-speed mixer in proportion and mixed at 85°C and 1350 rpm for 6 minutes to obtain the matrix premix.
[0039] Step S3, co-extrusion crosslinking: The matrix premix, grafted modified conductive carbon black, peroxide crosslinking agent and processing aid are added together to a twin-screw extruder with a length-to-diameter ratio of 40:1. The temperature from the feeding section to the melting section is 130°C, the temperature from the homogenization section to the die is 170°C, the screw speed is 300 rpm, and the total material residence time is 55 s. The peroxide is fully decomposed in the high-temperature melting section and completes the main crosslinking reaction. At the same time, based on its solubility difference in different microphase regions, it forms a crosslinking distribution tendency preferentially in the amorphous phase region.
[0040] Step S4, temperature-controlled crystallization and shaping: The extruded melt directly enters a segmented temperature-controlled cooling water bath; the first cooling section, i.e. the nucleation section, has a constant water temperature of 98℃, and the melt stays for 2.5 min; the second cooling section, i.e. the transverse crystal growth section, has a water temperature that linearly decreases to 88℃ at a rate of 3℃ / min, and is kept at a constant temperature for 6 min, inducing the in-situ growth of an interfacial crystalline layer with a thickness of 8-12 nm and a crystal interlayer spacing of 20-25 nm on the carbon black surface; the third cooling section, i.e. the shaping section, has a water temperature of 25℃, and rapidly cools and shapes the melt, with only trace amounts of subsequent crosslinking reactions occurring in the system.
[0041] Step S5 involves traction pelletizing to obtain cylindrical finished pellets with a diameter of 3-4 mm and a length of 3-5 mm.
[0042] Example 2: A cross-linked semiconductive shielding material, comprising the following components by weight: 82 parts olefin matrix resin, 18 parts oligomer grafted modified conductive carbon black, 1.2 parts peroxide cross-linking agent, and 0.7 parts processing aid. The proportions of the remaining components are the same as in Example 1.
[0043] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0044] Example 3: A cross-linked semiconductive shielding material, comprising the following components by mass: 82 parts olefin-based resin, 22 parts oligomer-grafted modified conductive carbon black, 1.2 parts peroxide cross-linking agent, and 0.7 parts processing aid. The proportions of the remaining components are the same as in Example 1.
[0045] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0046] Example 4: A cross-linked semiconductive shielding material, in which the bimodal crystallinity distribution of the ethylene-1-octene copolymer compound is 55:45 by mass, and the remaining composition ratios are the same as in Example 1.
[0047] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0048] Example 5: A cross-linked semiconductive shielding material, wherein the peroxide cross-linking agent is 1.0 part by mass, and the remaining composition ratios are the same as in Example 1.
[0049] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0050] Example 6: A cross-linked semi-conductive shielding material, in which, by mass, the number average molecular weight of the double-bonded 1-octene oligomer in the oligomer grafted modified conductive carbon black is 1500, and the grafting amount is 2.0% of the mass of the conductive furnace carbon black. The remaining composition ratios are the same as in Example 1.
[0051] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0052] Example 7: A cross-linked semiconductive shielding material, wherein, by mass parts, the 1-octene comonomer content of the highly crystalline ethylene-1-octene copolymer is 8%, the crystallinity is 55%, and the remaining composition ratios are the same as in Example 1.
[0053] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0054] Example 8: A cross-linked semi-conductive shielding material, comprising, by mass parts: 85 parts olefin-based resin, including 78 parts of a bimodal crystalline ethylene-1-octene copolymer compound and 7 parts high-density polyethylene; and 18 parts oligomer-grafted modified conductive carbon black. The proportions of the remaining components are the same as in Example 1.
[0055] The steps and process parameters of the preparation method of the cross-linked semiconductive shielding material are consistent with those of Example 1.
[0056] Comparative Example 1 is a cross-linked semi-conductive shielding material. The difference between it and Example 1 is that unmodified ordinary conductive furnace black is used instead of oligomer graft-modified conductive carbon black, while the other components are the same as in Example 1.
[0057] The preparation method of the cross-linked semiconductive shielding material follows the same steps as in Example 1.
[0058] Comparative Example 2, a cross-linked semiconductive shielding material, differs from Example 1 in that it uses a single-peak molecular weight ethylene-1-octene copolymer with a 1-octene comonomer content of 18%, a crystallinity of 25%, and a weight-average molecular weight of 150,000, replacing the bimodal crystallinity distribution ethylene-1-octene copolymer compound. Other components are the same as in Example 1.
[0059] The preparation method of the cross-linked semiconductive shielding material follows the same steps as in Example 1.
[0060] Comparative Example 3 is a cross-linked semiconductive shielding material. The difference between it and Example 1 is that it adopts a conventional stepwise cross-linking process. 0.5 parts of low-temperature initiator tert-butyl-2-ethylhexanoate peroxide is added to the first feeding port, and 0.7 parts of high-temperature cross-linking agent 2,5-dimethyl-2,5-di-tert-butylhexane peroxide is added to the second feeding port. Only the stepwise reaction in the time dimension is achieved, without phase-selective cross-linking effect. Other components are the same as in Example 1.
[0061] The preparation method of the cross-linked semiconductive shielding material is the same as that in Example 1, except that step S3 uses the stepwise cross-linking process described above.
[0062] Comparative Example 4 is a cross-linked semi-conductive shielding material, which differs from Example 1 in that it uses vinyltriethoxysilane-modified conductive carbon black, with the amount of silane being 1.5% of the mass of conductive furnace carbon black, replacing oligomer graft-modified conductive carbon black. Other components are the same as in Example 1.
[0063] The preparation method of the cross-linked semiconductive shielding material follows the same steps as in Example 1.
[0064] Performance testing: The cross-linked semiconductive shielding materials treated with Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to performance testing. The testing methods are as follows: Volume resistivity: Tested according to GB / T1410-2006 "Test methods for volume resistivity and surface resistivity of solid insulating materials", with a test voltage of DC 100V, a three-electrode system, an electrode diameter of 50mm, a test temperature of 20℃, and a sample thickness of 2mm.
[0065] Change rate of volume resistivity during thermal cycling: The temperature was cycled from -40℃ to 135℃ in a high and low temperature cycling test chamber for 200 cycles with a cycle period of 30 minutes. The volume resistivity before and after the cycle was tested according to GB / T1410-2006. The change rate was calculated by dividing the difference between the resistivity after the cycle and the resistivity before the cycle by the resistivity before the cycle and then multiplying by 100%.
[0066] Thermal aging volume resistivity change rate: An aging test was conducted using a 135℃ hot air aging chamber for 1500 hours. The volume resistivity before and after aging was tested according to GB / T1410-2006. The change rate was calculated by dividing the difference between the resistivity after aging and the resistivity before aging by the resistivity before aging and then multiplying by 100%.
[0067] Tensile strength and elongation at break: Tested according to GB / T1040.2-2006 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", with a tensile rate of 50 mm / min and using type 2 specimens.
[0068] Gel content: Xylene Soxhlet extraction was used with xylene as solvent, extraction temperature 140℃, extraction time 24h, and the sample was dried to constant weight after extraction. The fraction of insoluble matter in the total mass of the sample was calculated.
[0069] Carbon black retention rate: The toluene ultrasonic extraction method was used. The sample was cut into small pieces and placed in toluene. The sample was ultrasonically extracted at 250W for 2 hours. After centrifugation, the carbon black content of the sample before and after extraction was tested, and the carbon black retention rate was calculated. The higher the retention rate, the stronger the bonding between carbon black and the matrix interface.
[0070] Extrusion surface roughness: The surface roughness Ra value of the extruded strip was tested using a contact surface roughness tester with a sampling length of 5 mm.
[0071] The obtained test data are recorded in Table 1 below: Table 1 Performance test data for each embodiment and comparative example Performance test results show that Example 1 exhibits low volume resistivity, low resistivity change rate after thermal cycling and thermal aging, high carbon black retention, high tensile strength, and high overall performance. The topological entanglement and interfacial crystallization dual-anchored conductive network constructed through melt grafting of double-bond-terminated α-olefin oligomers can reduce the resistivity drift during thermal cycling and thermal aging, and enhance the interfacial bonding strength between carbon black and the matrix.
[0072] In Examples 2 and 3, the amount of carbon black was adjusted. Within the range of the amount defined in the claims, the volume resistivity decreased with the increase of carbon black amount. The resistivity change rate, carbon black retention rate and tensile strength remained stable after thermal cycling, which can be adapted to the shielding material requirements of different resistivity levels.
[0073] In Example 4, the composition ratio of the bimodal matrix was adjusted so that the volume resistivity, the rate of change of resistivity after thermal cycling, and the carbon black retention rate were all maintained at a high level. The ratio of bimodal crystallinity can be adjusted within the range of proportions defined in the claims according to processing and performance requirements.
[0074] In Example 5, the total amount of crosslinking agent was adjusted, and the gel content was reduced. However, the resistivity change rate after thermal cycling was still at a low level, and the dual anchoring structure could play a role under different crosslinking levels.
[0075] In Example 6, the number-average molecular weight and grafting amount of the oligomer were adjusted, and the volume resistivity, the rate of change of resistivity after thermal cycling, and the carbon black retention rate all met the requirements. The carbon black modification parameter range has process tolerance.
[0076] In Example 7, the content and crystallinity of the 1-octene comonomer in the high-crystallinity component were adjusted. The volume resistivity and the rate of change of resistivity after thermal cycling were similar to those in Example 1. The crystallinity parameters of the bimodal matrix can be adjusted appropriately according to the production line conditions.
[0077] In Example 8, increasing the proportion of matrix resin and reducing the amount of carbon black resulted in an increase in volume resistivity, but it remained within the applicable range for semiconductive shielding materials. The resistivity change rate and tensile strength after thermal cycling remained at a high level, and the conductive network construction mechanism could still function even with low carbon black content.
[0078] Comparative Example 1, using unmodified ordinary carbon black, showed a significantly increased volume resistivity, a significantly increased rate of resistivity change after thermal cycling and thermal aging, and a significantly decreased carbon black retention rate. All performance characteristics were significantly inferior to those of Example 1. After oligomer melt grafting modification, the resistivity change rate after thermal cycling was significantly reduced, and the carbon black retention rate was significantly increased. Oligomer melt grafting modification can reduce the resistivity drift and improve the interfacial bonding strength between carbon black and the matrix.
[0079] Comparative Example 2, using a single-peak molecular weight ethylene-1-octene copolymer, showed increased volume resistivity, significantly increased resistivity change rate after thermal cycling and thermal aging, decreased carbon black retention, and reduced electrical conductivity and mechanical properties. In contrast, using a bimodal crystallinity distribution ethylene-1-octene copolymer compound significantly reduced the resistivity change rate after thermal cycling and increased carbon black retention. The bimodal crystallinity distribution design promotes selective distribution of carbon black in the matrix and reduces resistivity drift.
[0080] Comparative Example 3, employing a conventional stepwise crosslinking process, showed an increase in volume resistivity, a significantly greater rate of resistivity change after thermal cycling, and a decrease in carbon black retention. It only achieved a stepwise reaction over time, lacking phase-selective crosslinking, and its performance was lower than that of Example 1. The amorphous phase-preferred crosslinking distribution, combined with interfacial crystallization anchoring, can further reduce resistivity drift while maintaining a high level of elongation at break.
[0081] Comparative Example 4, using conventional silane-modified carbon black, showed an increase in volume resistivity, a significantly increased rate of resistivity change after thermal cycling, and a decrease in carbon black retention, relying solely on weak interfacial bonding. In contrast, after oligomer melt grafting modification, the rate of resistivity change after thermal cycling was significantly reduced, and the carbon black retention was significantly increased. The long-term stability and interfacial bonding strength of the carbon-carbon bond grafted dual-anchoring structure were higher than those of the silane-modified structure.
[0082] By comparing and analyzing the relevant data in the table, it can be seen that the present invention, through the dual anchoring conductive network design of oligomer melt grafting, the phase region matching optimization of the bimodal crystallinity ethylene-α-olefin copolymer matrix, and the synergistic process of preferential crosslinking distribution of amorphous phase and segmented crystallization shaping, achieves better resistivity change rate, carbon black retention rate and tensile strength after thermal cycling than the comparative examples. This invention realizes the simultaneous improvement of the long-term conductivity stability, interfacial bonding strength and mechanical properties of the semiconductive shielding material, and can solve the problems of weak interfacial bonding between carbon black and matrix, large resistivity drift under thermal cycling, and easy migration and debonding during long-term operation in the prior art.
[0083] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0084] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A cross-linked semiconductive shielding material, characterized in that, By weight, it includes the following components: 80-85 parts olefin matrix resin, 18-22 parts oligomer graft modified conductive carbon black, 1.0-1.5 parts peroxide crosslinking agent, and 0.5-1.0 parts processing aid; The olefin-based resin is composed of a bimodal ethylene-1-octene copolymer blend and high-density polyethylene; the bimodal ethylene-1-octene copolymer blend is used in an amount of 72-80 parts, and is composed of a low-crystallinity ethylene-1-octene copolymer and a high-crystallinity ethylene-1-octene copolymer in a mass ratio of 55:45-65:35; the high-density polyethylene is used in an amount of 5-8 parts, and has a density of 0.945-0.955 g / cm³. 3 The melt index measured at 190℃ and 2.16kg load is 5-8g / 10min; the sum of the amounts of the bimodal crystallinity distribution ethylene-1-octene copolymer compound and the high-density polyethylene is 80-85 parts. The oligomer-grafted modified conductive carbon black is obtained by melt grafting of double-bond-terminated 1-octene oligomers onto conductive furnace black as the base material; the number average molecular weight of the double-bond-terminated 1-octene oligomers is 1500-2500, the double bond functionality is 1.8-2.0, and the grafting amount is 2.0%-3.0% of the mass of the conductive furnace black; The peroxide crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide; The processing aid consists of antioxidants and lubricants.
2. The cross-linked semiconductive shielding material according to claim 1, characterized in that, The low-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 24%–28%, a crystallinity of 5%–10%, and a weight-average molecular weight of 200,000–250,000; the high-crystallinity ethylene-1-octene copolymer has a 1-octene comonomer content of 8%–12%, a crystallinity of 45%–55%, and a weight-average molecular weight of 80,000–100,000.
3. The cross-linked semiconductive shielding material according to claim 1, characterized in that, The original particle size of the conductive furnace carbon black is 20–30 nm, the DBP absorbance is 38–42 mL / 100 g, and the specific surface area is 420–480 m². 2 / g; the melt grafting uses dicumyl peroxide as an initiator, and the amount is 0.1% to 0.2% of the mass of the conductive furnace carbon black.
4. The cross-linked semiconductive shielding material according to claim 1, characterized in that, The 1-minute half-life temperature of the 2,5-dimethyl-2,5-di-tert-butylperoxide is 178–182 °C.
5. The cross-linked semiconductive shielding material according to claim 1, characterized in that, The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], with an amount of 0.3 to 0.6 parts; the lubricant is zinc stearate, with an amount of 0.2 to 0.4 parts.
6. A method for preparing a cross-linked semiconductive shielding material as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: Step S1, Preparation of oligomer-grafted modified conductive carbon black: Conductive furnace black, double-bond-terminated 1-octene oligomer, and dicumyl peroxide are premixed and then fed into a twin-screw extruder for melt mechanochemical grafting. After extrusion and granulation, grafted modified carbon black is obtained; the amount of dicumyl peroxide is 0.1% to 0.2% of the mass of the conductive furnace black. Step S2, bimodal matrix premix: Low-crystallinity ethylene-1-octene copolymer, high-crystallinity ethylene-1-octene copolymer, and high-density polyethylene are added to a high-speed mixer in proportion and mixed evenly to obtain a matrix premix. Step S3, Blending Extrusion Crosslinking: The matrix premix, grafted modified conductive carbon black, peroxide crosslinking agent and processing aid are added to a twin-screw extruder, melt-blended and the main crosslinking reaction is completed. The crosslinking distribution tendency of amorphous phase is formed by taking advantage of the solubility difference of peroxide in different microphase regions, and the melt is extruded to obtain the melt. Step S4, temperature-controlled crystallization and shaping: The extruded melt enters a segmented temperature-controlled cooling water tank, where it is melt-blended and subjected to gradient cooling to complete the surface interface crystallization growth and system shaping of carbon black, accompanied by trace amounts of subsequent crosslinking reactions; Step S5 involves traction pelletizing to obtain cylindrical finished pellets with a diameter of 3-4 mm and a length of 3-5 mm.
7. The method for preparing a cross-linked semiconductive shielding material according to claim 6, characterized in that, In step S1, the length-to-diameter ratio of the twin-screw extruder is 40:1, the temperature of each section is 165-180℃, the screw speed is 300-350rpm, and the material residence time is 40-50s.
8. The method for preparing a cross-linked semiconductive shielding material according to claim 6, characterized in that, In step S2, the mixing temperature of the high-speed mixer is 80-90℃, the rotation speed is 1200-1500rpm, and the mixing time is 5-7min.
9. The method for preparing a cross-linked semiconductive shielding material according to claim 6, characterized in that, In step S3, the length-to-diameter ratio of the twin-screw extruder is 40:1, the temperature from the feeding section to the melting section is 120-140℃, the temperature from the homogenization section to the die is 165-180℃, the screw speed is 280-320 rpm, and the total residence time of the melt-blended and gradient-cooled material is 50-60s to ensure that the peroxide is fully decomposed in the melting section and completes the main cross-linking reaction.
10. The method for preparing a cross-linked semiconductive shielding material according to claim 6, characterized in that, The specific parameters for segmented temperature control in step S4 are as follows: The water temperature in the first cooling section, i.e. the nucleation section, is kept constant at 95–100°C, and the melt residence time is 2–3 minutes. The water temperature in the second cooling section, i.e. the transverse crystal growth section, is linearly reduced to 85-90℃ at a rate of 3℃ / min, and held at a constant temperature for 5-7 minutes. The water temperature in the third cooling section, also known as the shaping section, is 20–25°C.
